Climate-dependent chemical weathering of volcanic soils in Iceland - Óskarsson, Birgir V.; Riishuus, Morten S.; Arnalds, Ólafur (Geoderma, 2012)
The major element mobility within soil profiles of brown to gleyic Andosols that developed under diverse climatic conditions in Iceland is assessed. The volcanic soils were selected from areas with good monitoring of annual temperature and precipitation and the degree of weathering and elemental behavior is compared. Icelandic soils are subject to high fluxes of aeolian dust, and at times, to tephra ejecta from volcanic eruptions. The source of dust input is assessed for each profile based on comparison of the chemical signatures found in the less weathered upper horizons with those of volcanic systems supplying material to source areas. Results show that TiO2, Al2O3 and Fe2O3(T) and MnO are the least mobile species and generally found enriched within more mature horizons. The mobile base cations MgO, CaO and Na2O are depleted in these horizons as a result of chemical weathering during pedogenesis. Soils developed in colder climatic conditions with mean annual temperature (MAT) ∽−1°C give values for the Chemical Index of Weathering (CIW) of 37–45 that reflect only weak chemical weathering. Soils developed in milder climates (MAT=2–4°C) are more strongly affected by weathering (CIW=50–77). The parent material has CIW values of ∽37. Temperature is demonstrated as the dominant variable exerting control on the extent of weathering, with only minor mobilization following the incipient near-surface weathering stage. A robust linear relationship is found between CIW and model MAT (MAT=0.21CIW −8.93, R2=0.81). This climofunction can deliver proxy climate estimations from volcanic soils and paleosols of basaltic origin in cool to subarctic conditions (−2 to +6°C). ► We examine climate control on major element mobilization in Icelandic andosols. ► Mg, Ca, Na and Si are mobile, Ti, Al, Fe and Mn immobile relative to basalt parent. ► K and P show variable behavior, mostly due to fixation by organic matter. ► Incipient near-surface mobilization strongly exceeds post-burial weathering. ► A climofunction is given from correlation of weathering extent with temperature.